ANALISIS PERBAIKAN PERKERASAN JALAN DENGAN PERBAIKAN STANDAR DAN PELAPISAN TAMBAHAN (OVERLAY) SERTA BIAYA PENANGANANNYA (Studi Kasus Jalan di Area Kantor Dinas Perhubungan Kab.Sidoarjo) (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
This research is a case study of roads in the area of ​​the Transportation Service Office of Sidoarjo Regency. The purpose of this study is to analyze the types of road repairs with standard repairs and with additional coatings (overlays) and calculate the handling costs. The data analysis used is by using standard repair methods and additional coatings (overlays). Based on the results of the analysis and discussion, it can be concluded that the north side of the road was repaired by means of P2 (Local Asphalt Pelaburan), P5 (Pole Patching) and P6 (Grading), the west side road was repaired by means of P2 (Local Asphalt Pelaburan), P5 (Filling Patches). Holes) and P6 (Flattening), the middle side of the road is repaired by means of P2 (Local Asphalt Laying), P5 (Pole Patching) and P6 (Smoothing), The south side road is repaired by means of P2 (Local Asphalt Laying), P3 (Coating Cracks), P4 (Filling of Cracks), P5 (Filling Holes) and P6 (Smoothing), The east side of the road is repaired by means of P2 (Local Asphalt Filling), P3 (Filling Cracks), P4 (Filling Cracks), P5 (Filling Holes) ) and P6 (Grading) and for additional coating the volume of road repair work covering an area of ​​4,440 m² with a thickness of 8 cm for a design life of 10 years using the type of material Laston MS.744, while the cost of repairing road damage in the Ka area Office of Transportation of Sidoarjo Regency with standard improvement of Rp. 574,554,000.00 and the cost of repairing roads with additional overlays of Rp. 5,498,496,000.00